Antimicrobial resistance surveillance of Escherichia coli from chickens in the Qinghai Plateau of China - Tang, Biao; Wang, Jingge; Zheng, Xue; Chang, Jiang; Ma, Jiangang; Wang, Juan; Ji, Xiaofeng; Yang, Hua; Ding, Baoan (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) may lead to worldwide epidemics through human activities and natural transmission, posing a global public safety threat. Colistin resistance mediated by the mcr-1 gene is the most prevalent among animal-derived Escherichia coli, and mcr-1-carrying E. coli have been frequently detected in central-eastern China. However, animal-derived E. coli with AMR and the prevalence of mcr-1 in the Qinghai Plateau have been rarely investigated. Herein, 375 stool samples were collected from 13 poultry farms in Qinghai Province and 346 E. coli strains were isolated, of which eight carried mcr-1. The AMR rates of the E. coli strains to ampicillin, amoxicillin/clavulanic acid, and tetracycline were all above 90%, and the resistance rates to ciprofloxacin, cefotaxime, ceftiofur, and florfenicol were above 70%. Multidrug-resistant strains accounted for 95.66% of the total isolates. Twelve E. coli strains showed colistin resistance, from which a total of 46 AMR genes and 36 virulence factors were identified through whole-genome sequencing. The mcr-1 gene resided on the IncHI2, IncI2-type and IncY-type plasmids, and mcr-1 was located in the nikA-nikB-mcr-1-pap2 gene cassette (three strains) or the pap2-mcr-1-ISApl1 structure (one strain). Completed IncI2-type plasmid pMCR4D31–3 sequence (62,259 bp) revealed that it may cause the horizontal transmission of mcr-1 and may increase the risk of its spread through the food chain. Taken together, the AMR of chicken-derived E. coli in the plateau is of concern, suggesting that it is very necessary for us to strengthen the surveillance in various regions under the background of one health.